Transluminal migration of oesophageal foreign bodies: a series of three patients/ Lim lu Tong ... [et al.] - Tong, Lim Iu; Ming, Ong Fei; Ramasamy, Viji; Mohan Singh, Avatar Singh; Mohamad, Irfan (Faculty of Medicine, 2023)
Inadvertent ingestion of foreign bodies, particularly fish bone, are a common complaint in the otolaryngology emergency practices in Southeast Asia. Due to its thin, linear, and sharp pointed end, fish bone has the potential to penetrate through the oesophagus wall, or migrate extraluminally towards the surrounding structures in the neck, resulting in bizarre and lethal complications. We present an unusual case of extraluminal migration of foreign body (FB) and 2 cases of completely embedded FB in the oesophagus wall. We aim to share our experience in both conservative approach and transcervical approach for these difficult clinical problems. All of them have minimal rigid oesophagoscopy findings but possess the radiological evidence of FB. Computed tomography scan have higher sensitivity and provide good preoperative guidance, it should be done early and performed in the event of negative endoscopic evaluation. Prompt diagnosis and early retrieval of FB can significantly reduce morbidity and mortality.